2012
DOI: 10.1159/000341390
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Stanniocalcin 1 as a Potential Biomarker of Gastric Cancer

Abstract: Objective: We investigated stanniocalcin 1 (STC 1) expression to assess its clinical utility as a blood marker in patients with gastric cancer and evaluated its biological impact in terms of tumor aggressiveness. Methods: Blood specimens from 93 patients with gastric cancer and 21 normal healthy volunteers were assessed by quantitative reverse transcription-polymerase chain reaction for STC 1 mRNA expression. Results: The relative numbers of STC 1 mRNA copies were significantly higher in gastric cancer cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 49 publications
3
15
2
Order By: Relevance
“…We found significantly greater levels of STC1 and STC2 mRNA in the PB samples of LSCC patients than those of healthy volunteers. These data are consistent with observations reported for gastric cancer [16], [17], esophageal squamous cell carcinoma [18], and non-small cell lung cancer [12]. Furthermore, we investigated whether STC1 or STC2 levels in LSCC tumors were potential molecular markers of prognosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found significantly greater levels of STC1 and STC2 mRNA in the PB samples of LSCC patients than those of healthy volunteers. These data are consistent with observations reported for gastric cancer [16], [17], esophageal squamous cell carcinoma [18], and non-small cell lung cancer [12]. Furthermore, we investigated whether STC1 or STC2 levels in LSCC tumors were potential molecular markers of prognosis.…”
Section: Discussionsupporting
confidence: 90%
“…STC1 and STC2 are involved in various biological mechanisms of tumor progression [8], [11][14]. Both STC1 and STC2 are considered to be promising biomarkers, because their mRNA levels are elevated in the PB of cancer patients [12], [16][18]. However, little is known regarding the clinical significance of STC1 and STC2 expression levels in PB from patients with LSCC.…”
Section: Discussionmentioning
confidence: 99%
“…This gene could be a target also of Hsa-miR-188-5p, already described in rectal cancer [118]. Hsa-miR-532-5p regulates also stanniocalcin 2 (STC2): it is a glycoprotein hormone that plays an important role in calcium and phosphate homeostasis and is considered a tumor progression predictor for gastric cancer [119] and breast carcinoma [120]. Concerning Hsa-miR-188-5p, it already results to be overexpressed in UVB irradiated mouse skin [121], suggesting a potential role of this miR in response to oxidative stress linked to radiation.…”
Section: Discussionmentioning
confidence: 97%
“…Mitochondrial localization of STC1 binding was also demonstrated using STC-alkaline phosphatase fusion protein in biochemical analyses and in situ ligand binding in nephron cells and liver hepatocytes (78). On the other hand, cytoplasmic STC1 staining was reported for human gastric cancer, esophageal squamous cell carcinomas, breast carcinomas, and ovarian carcinomas (32,34,36,79). In the current study, the pattern of STC1 expression as demonstrated by immunohistochemistry was highly variable; STC1 expression was low in normal mouse thyroid epithelial cells and was focally found in the cytoplasm of mouse adenomas, while relatively high expression was found in normal human thyroid follicular cells, both mainly found in nuclei.…”
Section: Discussionmentioning
confidence: 44%